Investigation of food losses in cold cargo transports: A case study of cold cargo chain supply chains of fresh foodstuff to Sweden - Jacobsson, Isa; Norlin, Anton (My University, 2024)
The transportation of perishable goods within cold supply chains is important for maintaining food quality and minimizing food losses. Despite technological advancements in cold chain logistics, challenges connected to temperature deviations may occur. This report investigates the cold supply chain logistics of food transports to and in Sweden, with a primary focus on operational, technical, and regulatory challenges with food losses. The report solely focused on perishable goods such as food stuff and did not take return supply chains into account, or other, non-edible goods in cold transports. The report has been based on a case study analysis, incorporating perspectives from different companies operating within the cold chain supply. Research questions address companies' alignment with Sustainable Development Goals and regulations, operational aspects of refrigerated cargo handling, and initiatives for better energy efficiency in refrigerated transportations. Findings show that the companies are compatible with regulatory frameworks, despite this there has been recurring evidence which shows human errors contributing to food loss, primarily related to temperature deviations. Operational improvements are discussed in existing literature, but operational aspects hinder implementation. Initiatives for energy efficiency are discussed, primarily related to the fuel consumption of performed transports and not necessarily of the cooling unit’s consumption. In conclusion, although companies show compliance with regulatory frameworks, there exists a need for continuous legislative improvement from the decision makers, in order to minimize food loss. Operational challenges, particularly human errors, require attention and innovative solutions to minimize food losses. Initiatives for energy efficiency are shown by all interviewed companies but are varying in regard to different focus points related to the companies’ respective activities.
Keywords: Reefer; refrigerated unit; food losses; food waste; emission; energy consumption; transportation; kylaggregat; matförluster; matavfall; utsläpp; energiförbrukning; transporter